Potential infectivity of blood from HBsAG asymptomatic carriers due to the presence of HBV-DNA and comparison with other markers of hbv infection Potencial de infectividade em sangue de portadores assintomáticos de HBsAg caracterizado pela presença de HBV-DNA e comparação com outros marcadores da Hepatite B. - M. Valeria Tedeschi; Cláudia Figueiredo Padilla; Iná Ferraz De Camargo; Clara F. Tachibana Yoshida (Revista do Instituto de Medicina Tropical de São Paulo, 1989)
Serum samples from 356 HBsAg positive asymptomatic carriers, which were titrated by reverse passive hemagglutination, were analysed for the presence of HBV-DNA, HBsAg and IgM anti-HBc. The samples were divided in three classes, according to the titers of HBsAg and IgM anti-HBc and the distribution of HBV-DNA and HBsAg among these classes was studied. In the high titer class of HBsAg, 65% of samples have one or both markers against only 19% in the low titer class. From the total of 356 samples, 121 gave positive results for IgM anti-HBc (33.9%). From these, 38.9% of HBV-DNA and 47.9% of HBeAg were observed, whereas in samples with absence of IgM anti-HBc, 18.3% and 16.6% were respectively found. A higher frequency of agreement between all these markers was found in the class of high titers of HBsAg; however, HBV-DNA was detected in the low titer class of HBsAg and little or no IgM anti-HBc, showing potential blood infectivity even in HBsAg positive borderline samples. Em 356 soros HBsAg positivos de portadores assintomáticos, titulados por hemaglutinação passiva reversa, foi analisada a presença de HBV DNA, HBeAg e IgM anti-HBc, da seguinte forma: as amostras foram divididas em três classes de acordo com o título de HBsAg e IgM anti-HBc e foi verificada a distribuição de HBV DNA e HBsAg nestas classes. Em amostras com títulos elevados de HBsAg, 65% das amostras tiveram um ou ambos os marcadores HBV-DNA e HBsAg e as mesmas foram encontradas em apenas 19% das amostras com baixo título de HBsAg. Do total de 356 amostras, 121 foram positivas para IgM anti-HBc (33.9%). Destas, 38.9% de HBV-DNA e 47.9% de HBeAg foram observadas, ao passo que em amostras com ausência de IgM anti-HBc, 18.3% e 16.6% foram respectivamente encontrados. A concordância entre os três marcadores foi encontrada em. amostras com alto título de HBsAg, entretanto HBV-DNA foi também detectado em grupo de baixo título de HBsAg na ausência de IgM anti-HBc ou em níveis baixos, mostrando o potencial de infectividade mesmo em amostras de HBsAg com ...